COMPARISON OF TOTAL CHOLESTEROL AND HDL CHOLESTEROL RATIO BY TERTILE OF WAIST HIP RATIO IN POSTMENOPAUSAL WOMEN - Sultan, Noorin; Badar, Ahmed; Nawaz, Mohammad; Sultan, Ambreen; Fayaz, Mohammad; Baseer, Abdul (Journal of Ayub Medical College Abbottabad, 1998)
The waist hip ratio (WHR)is a useful parameter to determine the distribution of fat. In women the fat is predominant in gluteal and femoral regions under the effects of oestrogen. After menopause oestrogen deficiency occurs and women become prone to masculine type of adipose tissue distribution that is high waist /hip circumference ratio. In addition to this the relative '˜immunity' from CHD in female gender finishes at menopause. This study was aimed at determining a relation between WHR and TC/HDL-C ratio in postmenopausal women. The results of this study indicate that most (64%) postmenopausal women of the study population were having a large WHR and also showed TC/HDL-C ratios that were significantly more than the postmenopausal women with less WHR. In addition, the mean TC/HDL-C ratio in this group was above the danger limit for this value, which suggests that a large percentage of our postmenopausal women are at a higher risk of CHD.